Latitude and Altitude Influence Secondary Metabolite Production in Peripheral Alpine Populations of the Mediterranean Species Lavandula angustifolia Mill. - Demasi, Sonia; Caser, Matteo; Lonati, Michele; Cioni, Pier L.; Pistelli, Luisa; Najar, Basma; Scariot, Valentina (Frontiers in Plant Science, 2018)
Lavandula angustifolia Mill. has a great economic importance in perfumery, cosmetics, food manufacturing, aromatherapy and pharmaceutical industry. This species finds its phytosociological optimum in the sub-Mediterranean region. Latitudinal and altitudinal gradients are expected to affect species diversification in peripheral alpine populations. In this study, phenotypic traits including morphometric parameters, volatile organic compounds (VOCs) and essential oils (EOs) were analyzed in lavender peripheral populations selected in order to explore different ecological conditions. Plants were cultivated under uniform conditions to observe variations due to the genetic adaptation to native environments and to exclude the short-term response to environmental factors. Results showed qualitatively and quantitatively intra-specific variations in secondary metabolites, mainly along the latitudinal gradient, while minor effect was attributable to the altitude. This latter affected more the morphometric parameters. As the latitude augmented, VOCs showed lower content of monoterpene hydrocarbon (mh) and higher content of oxygenated monoterpenes (om); whereas EOs showed higher content of mh and non-terpene derivatives (nt) and lower content of sesquiterpene hydrocarbons (sh). Lavender aroma and EO composition varied in every population, for a total of 88 and 104 compounds identified, respectively. Eleven and 13 compounds were responsible for 95% of the dissimilarity, with linalool, linalyl acetate and 1,8-cineole as major contributors. As the latitude augmented, linalool decreased and 1,8-cineole increased while linalyl acetate content was unaffected. These results are discussed with regards to the potential adoption of the lavender peripheral alpine populations for the improvement of quality and productivity of lavender cultivations, especially in mountainous areas.